“I feel like a fish out of water”: interpreting the occupational stress and well-being experiences of professional classical musicians - Willis, Simone; Mellick, Mikel; Neil, Rich; Wasley, David (Frontiers in Psychology, 2024)
Introduction Professional classical musicians operate within a highly demanding environment, which includes organizational, social, and emotional demands. When not effectively coped with, these demands may cause stress and negatively impact well-being. This qualitative study explored the perceived stress and well-being experiences of professional classical musicians through a transactional theory of stress. The study employed a double hermeneutic interpretation of the lived experiences of the perceived demands faced, stress appraisals made, resources used, and the influence on well-being. Methods Six professional classical musicians were purposefully selected for participation. Semi-structured interviews were conducted and participants reflected on two events: one they perceived as a positive experience and one that was negative. Transcripts were analyzed using Interpretative Phenomenological Analysis and Group Experiential Themes emerged. Results Three Group Experiential Themes were identified: (a) Performance Demands; (b) Organizational Demands; and, (c) Relationship Demands. Participants predominantly appraised demands as a threat. A small number of demands were appraised as a challenge or benefit, and the fewest demands were appraised as causing harm or loss. Participants’ appraisals were informed by underlying properties of stress appraisal such as self and other comparison, and preparation. Participants often relied on personal resources as opposed to available workplace resources. They perceived well-being to relate to stress appraisals with participants experiencing acute and long-term outcomes. Discussion This study offers insight into the lived experience of the occupational stress process within professional classical musicians. The findings demonstrate that organizational interventions targeted at continuing professional development and social support are appropriate to help musicians cope more effectively with demands.